2008
DOI: 10.1094/pdis-92-1-0175c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Xylella fastidiosa in Avocado in Costa Rica

Abstract: Since the late 1990s, chlorotic mottling, marginal scorch, deformation of leaves, defoliation, shortening of internodes, and branch dieback have been observed in avocado trees (Persea americana Mill.) in Costa Rica. The symptoms are not uniformly distributed in the tree, so some branches are symptomatic while others are not. These symptoms are similar to several leaf scorch diseases caused by the bacterium Xylella fastidiosa Wells (2,4). This bacterium has been detected in coffee and citrus plants in Costa Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The most economically important diseases caused by X. fastidiosa are Pierce's disease of grape (PD) and citrus variegated chlorosis (CVC) of citrus species, both of which have received more attention by far than the many other diseases caused by this pathogen. Alfalfa, peach, plum, almond, elm, coffee, sycamore, oak, maple, pear are among the many other plant species for which diseases caused by X. fastidiosa are described, and the pathogen can be detected in hundreds of asymptomatic plant species (14,27,57,59,60,62,64,65,78,83,93,125). This pathogen is obligately vector-transmitted from one plant to another by various xylem sap-feeding insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most economically important diseases caused by X. fastidiosa are Pierce's disease of grape (PD) and citrus variegated chlorosis (CVC) of citrus species, both of which have received more attention by far than the many other diseases caused by this pathogen. Alfalfa, peach, plum, almond, elm, coffee, sycamore, oak, maple, pear are among the many other plant species for which diseases caused by X. fastidiosa are described, and the pathogen can be detected in hundreds of asymptomatic plant species (14,27,57,59,60,62,64,65,78,83,93,125). This pathogen is obligately vector-transmitted from one plant to another by various xylem sap-feeding insects.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the study of PD has dramatically increased since the last reviews of this pathogen, which focused mostly on descriptions of symptom development and etiology of disease (64,65,93). Perhaps due to the increasing attention to this pathogen, as well as better means of detection and discrimination of its many strains, this pathogen is being detected in large numbers of new host plant species in California and elsewhere (27,60,78,83); whether these numbers represent a broadening of its host range due to pathogen evolution or introduction of novel strains, or simply an appreciation of is exceptionally wide host range is unknown. Like-wise, the outbreak of CVC in Brazil has also stimulated extensive study of the strains that cause that disease, and led to the complete sequencing of the genome of a CVC strain of X. fastidiosa, the first plant pathogenic bacterium to be sequenced (111).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports in the past few years have revealed that X. fastidiosa is associated with diseases in a growing number of plant hosts (Almeida et al, 2005;Baumgartner and Warren, 2005;Hernandez-Martinez et al, 2007;Montero-Astua et al, 2008;Myers et al, 2007;Randall et al, 2007). No reports, however, specifically describe the aforementioned blueberry disease.…”
mentioning
confidence: 99%
“…Almeida et al (2005) showed that Homalodisca coagulata was able to inoculate X. fastidiosa into dormant grapes, although field acquisition experiments did not result in transmission. Montero-Astua et al (2008) reported the finding of X. fastidiosa in avocado plants in Costa Rica based on the positive results of enzyme-linked immunosorbent assay (ELISA) and PCR, although attempts to cultivate the bacterium in periwinkle wilt (PW) medium (Davis et al, 1981) and buffered charcoal yeast extract medium (Feeley et al, 1979;Raju et al, 1982) were negative.…”
mentioning
confidence: 99%
“…Hopkins, ; Purcell and Saunders, ; Hopkins and Purcell, ), while in other plants, it can be a serious pathogen causing a wilting or scorching disease (EFSA PLH Panel, ). X. fastidiosa is reported from many countries and from a great number of host plants including important tree crops like coffee (Rodriguez et al., ), citrus (Hartung et al., ; Aguilar et al., ), avocado (Montero‐Astua et al., ) and grapevine (Hill and Purcell, ; Aguilar et al., ). It can also infect many ornamental plants, like Nerium oleander (Oleander, Purcell et al., ; Montero‐Astua et al., ) and Polygala myrtifolia (Saponari et al., ; Martelli, ).…”
Section: Assessmentmentioning
confidence: 99%